Color quality improvement of Cherax quadricarinatus with dragon fruit peel meal utilization - Rakhmawati Rakhmawati; Tulas Aprilia; Nur Indariyanti; Andre Saputra; Eulis Marlina (Depik, 2023)
This study aims to determine the effect of dragon fruit peel meal utilization in the diet to improving the color quality of freshwater crayfish (Cherax quadricarinatus). This research was done from May to June 2022 at the Lampung State Polytechnic Fisheries Laboratory. The test animals used were freshwater crayfish with an average weight of 6.7 6.8 g/crayfish and a stocking density of 7 crayfish/aquarium. Feeding with a feeding rate of 3% twice a day. The experimental design used was a completely randomized design with 5 treatments and 3 repetitions. The treatments were A = commercial feed (control), B = 5% dose, C = 10% dose, D = 15% dose, E = 20% dose. The parameters observed in this study were an increase in color quality and water quality. The results of this study indicate that the difference in the dose of red dragon fruit peel meal in the diets can have a significant effect on the color brightness of freshwater crayfish (86.01 in claws and 87.59 in Chepalotorax to teslon). The conclusion of this research is that supplementation of red dragon fruit peel meal mainly at a dose of 10% in the feed can improve the color quality of freshwater crayfish from brown to bluish color.Keywords:Dragon fruit peel meal UtilizationDietColor qualityCherax quadricarinatus